PEMBINAAN OLAHRAGA BELA DIRI WUSHU DI KOTA SALATIGA TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2013)
The purpose of this study was to determine the exercise program, the quality of the coach, the state organizations, facilities and infrastructure and the funds used in the development of Wushu martial arts as the city of Salatiga. This research uses descriptive qualitative method with a sample board Indonesian Wushu Salatiga, Shceuder gym, gym Putra Nusantara and wushu teaching institution. Collecting data using observations, interviews and documentation of the data sources in the form of the informant Indonesian Wushu Salatiga administrators, coaches and athletes. As documents or evidence in the form of a plaque, photograph, governance structure and others.. Results of research on coaching wushu wushu athletes in the gym as the city of Salatiga is (1) Fostering achievement wushu wushu athletes in the gym as the city of Salatiga Pretty good, (2) The state of organization is going well, both of WI and gym are still running coaching current as well coordinated, is still a simple, family and openness among its members, (3)) The quality is good but the coaches need additional coaches . Conclusion that this guidance is given regarding (1) Development of wushu martial arts gym in a pretty good Salatiga, by adopting a structured sustainable development, (2) Increase cooperation with institutions and other parties in order to explore funding, (3) coaches, facilities and infrastructure need to be supplemented and complemented.